SARS-CoV-2 antibodies in Colombian urban area: follow-up on occupational groups - Colmenares-Mejia, Claudia C.; Quintero-Lesmes, Doris C.; Serrano, Norma C.; Meneses, Ligia; Salazar Acosta, Isail; Idrovo, Alvaro J.; Sanabria-Echeverry, Duván Y.; Cordero-Rebolledo, Helmer; Castillo, Victor (Revista Cuidarte, 2025)
Highlights • This study reveals diverse levels of SARS-CoV-2 exposure among occupational groups in Bucaramanga, highlighting the vulnerability of informal workers. • Adjusted seroprevalence progressively increased during the pandemic, reaching 29.2% in the third round among workers in the Bucaramanga Metropolitan Area. • Healthcare workers accounted for over 50% of the participants, emphasizing their significant involvement in the study. • Hybrid immunity emerges as a factor more associated with infection than vaccination, underscoring the importance of targeted interventions to protect vulnerable groups. Introduction: Globally, the COVID-19 pandemic typically relied on reported cases, but a more comprehensive view emerges from antibody identification. A 2020 national study in Bucaramanga revealed diverse SARS-CoV-2 exposure levels among occupational groups, emphasizing the vulnerability of informal workers. Objective: This study estimates adjusted seroprevalence and seroincidence of SARS-CoV-2 antibodies (IgM and IgG) among occupational groups in the Bucaramanga Metropolitan Area (Colombia) in three different moments of the pandemic. Materials and Methods: The prospective cohort study was conducted from September 2020 to October 2021, comprising three rounds. Each round gathered demographic data, medical history, COVID exposure or diagnosis, and vaccination status from workers across various occupational groups in Bucaramanga and its metropolitan area. Immunoglobulins G and M were assessed in each round, and adjusted seroprevalence was calculated. Results: A total of 1,013 subjects participated in all rounds. Healthcare workers accounted for more than 50% of all participants. By Round 3, 93.6% (n = 948) of participants had received the vaccination. Adjusted seroprevalence increased progressively (Round 1: 15.9% [95%CI 13.7–18.2]; Round 2: 18.4% [95%CI 16.0–20.7]; Round 3: 29.2% [95%CI 26.4–31.9]). Seroincidence for IgM/IgG positivity by Round 3 was 26.2% (95%CI 20.7–31.6). Discussion: The progressive increase in adjusted SARS-CoV-2 seroprevalence among workers in the Metropolitan Area of Bucaramanga is highlighted, with a notable prevalence among healthcare workers. Conclusions: The study underscores the prevalence of SARS-CoV-2 infection among workers in the Bucaramanga Metropolitan Area, emphasizing the role of hybrid immunity following vaccination in infection rates. Continued monitoring and tailored interventions are vital for protecting vulnerable populations. How to cite this article: Colmenares-Mejía Claudia C, Quintero-Lesmes Doris C, Serrano Norma C, Meneses Ligia, Salazar Acosta Isail, Idrovo Álvaro J, Sanabria-Echeverry Duván Y, Cordero Rebolledo Helmer, Castillo Víctor. SARS-CoV-2 antibodies in Colombian urban area: follow-up on occupational groups. Revista Cuidarte. 2025;16(2):e4029. https://doi.org/10.15649/cuidarte.4029